O regime de substituição tributária nas operações com rochas ornamentais no Estado do Ceará – uma análise empírica do impacto do decreto n° 30.256/2010 - Louzada, João Marcos de Campos (2015)
With the intention of encouraging the sector of ornamental rocks in Ceará, SEFAZCE established the tax substitution system for this segment. The intention of the new tax policy aimed to establish an operational and simplified tax regime, provide greater competitiveness in the domestic market, neutralize unfair competition between state taxpayers and develop the industrial park industry. To check the impact of this new tax policy in the sector's revenues, applied econometric methodology of the difference estimator in differences in a database the years 2003-2013 of the State of Ceará taxpayers and considered the Decree 30.256/2010 for an event based on comparison between before and after. Overall, there was revenue growth for industry taxpayers in the payment scheme EPP and MICROEMPRESA, and it was not possible to conclude whether there was an impact on revenue for taxpayers NORMAL payment scheme.